Application of forensic entomology in crime scene investigations in Malaysia / Kavitha Rajagopal - Rajagopal, Kavitha (2013)
Forensic entomology is the application and study of insect biology to criminal matters. One of the most important aspects of forensic entomology is the usage of maggot found in dead human body to determine the post-mortem interval (PMI). Based on the number of maggot sent for PMI determination, the application of forensic entomology in crime scene investigation is still unsatisfactory in Malaysia. Hence the present study was the first to conduct a questionnaire survey to determine the degree of knowledge and awareness of forensic entomology in Malaysia. A total of 402 participants comprising of the crime scene police officers, pathologists who did the post-mortem examination, scientific officers and university students who have taken forensic science as their main subjects were included. Results showed that pathologists, scientific officers and university students have better awareness and knowledge of forensic entomology than the crime scene police officers. Hence more professional training is needed particularly among the crime scene police officers. The survey identified two major obstacles that may hinder the growth of forensic entomology in Malaysia which are the lack of information on the forensically important fly as well as the lack of expertise in species identification. Nevertheless the survey revealed a bright prospect for forensic entomology as evidenced by increased awareness of its importance and interest in the younger generation. The present study was the first to apply both morphological and molecular methods for fly species identification in samples collected from crime scene investigation in Malaysia. A total of 50 cases from December 2008 to March 2010 were included. The present study confirmed the usefulness of molecular method based on cytochrome oxidase genes sequencing as a complementary tool in assisting fly species identification. Phylogenetic analyses confirmed the presence of Chrysomya megacephala, Chrysomya rufifacies, Chrysomya nigripes, Hemipyrellia ligurriens and Sarcophaga ruficornis. In addition, one ‘unknown’ species of blow fly was discovered. The application of molecular method has proven to be more advantageous in the case of immature maggot and egg. Due to the lack of experienced entomologist in Malaysia, it is recommended that molecular method should be widely applied. iii Since Chrysomya megacephala and Chrysomya rufifacies was found to be the two most prominent fly species recovered in crime scene investigation, DNA barcoding was done for each life cycle stage of both blow flies namely egg, 1st instar, 2nd instar, 3rd instar, pupae, empty puparium and adult fly. The present study confirms that all life cycle stage of a particular species of fly yield identical DNA barcode and hence all the stages can be used for accurate species identification. The present study represents an initial effort to establish a DNA barcoding for forensically important blow fly in Malaysia. However, the effective use of DNA barcoding would require an expert system of integrated information whereby species names and their respective DNA barcodes are coupled with data of life cycle and geographic distributions.